The Impact of AI Chat-GPT Dependence on High School Teenagers in Bandung City - Uyun, Aip Syaepul; Muttakin, Jaenal (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The development of Artificial Intelligence (AI) technology, especially ChatGPT, has had a major impact on the world of education, including among high school students. This study aims to identify the level of ChatGPT usage and the perceptions of high school teenagers in Bandung City regarding the positive and negative impacts of its use. Using a qualitative descriptive approach, data were collected through questionnaires, interviews, and documentation from 100 respondents selected using stratified random sampling. The results showed that 91% of students use ChatGPT for academic purposes, but only 35% understand how to use it wisely. As many as 77% of respondents are aware of the potential risk of dependency, but many still use it without critical consideration. These findings indicate that although AI can increase productivity and efficiency in learning, ignorance in its use has the potential to interfere with the development of critical and analytical thinking skills, social and collaborative development, and the low accuracy of information generated by Chat-GPT. Therefore, digital literacy and an educational approach are needed that prioritize the use of AI ethically and responsibly in the era of Society 5.0.